INTERNATIONAL TRANSPORT COMPANIES IN THE BALTIC COUNTRIES: INTERNATIONALIZATION MOTIVES AND BARRIERS - Trinkunienė, Sandra; Aksomitienė, Jūratė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Internationalization of companies is a necessity on purpose to play an active role in the international market and maintain a competitive advantage. The presented paper aims to reveal barriers and motives for a company‘s internationalization in the Baltic countries. The perceptions of internationalized and non-internationalized firms were assessed. The paper reveals the main motives and barriers of foreign transport and logistics companies for internationalization. All the Baltic countries compete for DFI and seek to demonstrate that they are ideal locations for foreign transport and logistics companies to establish an enterprise or choose another internationalization mode.The authors disclosed why service firms internationalize to the Baltic countries. The main attractiveness factors of the transport and logistics market in the Baltic countries, internationalization motives and barriers were compared. The framework has been approved by Scandinavian and Central European transport companies that have expanded their business in the Baltic countries. Theoretical and empirical results are beneficial for transport companies seeking to internationalize their activities in Lithuania, Latvia or Estonia.